Effects of intimate partner violence and homophobic bullying on ART adherence among young Thai men who have sex with men: a causal mediation analysis - Doug H. Cheung; Alexis N. Reeves; Worawalan Waratworawan; Yamol Kongjareon; Thomas E. Guadamuz (BMC Public Health)
Abstract Background Adherence to antiretroviral therapy is crucial for determining health outcomes and secondary HIV transmission among people living with HIV/AIDS. Young men who have sex with men (YMSM) living with HIV are often challenged by the prevailing experiences of psychosocial stressors such as intimate partner violence and homophobic bullying, which may negatively affect their HIV care engagement. Methods This study is the first to utilize a prospective cohort design (N = 185) involving YMSM living with HIV in Thailand. We examined the effects of intimate partner violence and homophobic bullying on ART adherence. We also tested the mediating effect of depression on the relationship between intimate partner violence and homophobic bullying and ART adherence. Results We found that intimate partner violence (AOR: 2.58, 95% CI: 1.13, 5.42) and homophobic bullying (AOR: 2.40, 95% CI: 1.26, 4.48) were associated with subsequent ART nonadherence. Moreover, depression partially mediated 17.4% (95% CI: 0.75%–56%) of the effect of homophobic bullying on ART nonadherence. Conclusions The results suggest that tailored interventions to optimize ART adherence should address the impact of intimate partner violence and homophobic bullying among YMSM living with HIV. Screening and subsequent treatment of depression alone may not be sufficient to address the effects of intimate partner violence, homophobic bullying, and possibly other MSM-specific psychosocial stressors on ART adherence.